Peningkatan produktivitas ternak Domba/Kambing melalui penyuluhan dan pelatihan teknologi pengolahan pakan - Rina Nuryati; Faqihuddin Faqihuddin; Cici Aulia Permata Bunda; Januar Arifin Ruslan (Riau Journal of Empowerment, 2021)
Tasikmalaya regency has great potential in the development of the livestock sector due to land use which is dominated by agricultural activities as a producer of forage. The current problem is the supply of forage which is influenced by the season. This service program aims to overcome these problems so as to increase the productivity of the livestock business. This service includes several stages, namely counseling, training, monitoring and evaluation and reporting. The time and place of the activity is from 5th June to 15th July 2021 in Setiawaras Village, Tasikmalaya Regency. Extension activities and training on feed processing with M-Bio technology have a positive impact in terms of the quantity and quality of feed. The use of local ingredients and M-Bio produces feed that can be stored for a week with complete nutrient content. In the long term, this activity will increase knowledge, skills and independence of farmers. Results of evaluation show attitude of farmers who are enthusiastic and satisfied with this activity.